Psychological culture and psychoculture: common features and differences - Ардашова, Я. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article analyzes the disclosing features of using such definitions as «psychoculture» and «psychological culture». The differences in understanding these definitions and revealing features of the researching phenomenons are shown.